Font Legal Protection for Child Victims of Artificial Intelligence (AI)-Based Exploitation in Indonesia: Regulatory Challenges and Strengthening the Digital Legal System - Salisah Salsabilla (Green Publisher, 2025)
The development of Artificial Intelligence (AI) technology provides significant benefits to society, but also poses new threats to the protection of children's rights. One such threat is the exploitation of children's digital identities through deepfake technology, biometric data theft, and the manipulation of digital content without consent. This study aims to analyze the legal regulations in Indonesia regarding child protection from AI-based exploitation and formulate efforts to strengthen the digital legal system in the future. This study uses a normative legal research method with a statutory, conceptual, and comparative approach. The results indicate that existing regulations, such as the Child Protection Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law, do not specifically regulate AI-based child exploitation. Therefore, legal reform is needed through the creation of adaptive regulations, strengthened oversight of digital platforms, and increased public digital literacy as a preventative measure. This research is expected to form the basis for developing legal policies that are responsive to developments in digital technology.